Optimization of PLGA nanoparticles formulation containing L-DOPA by applying the central composite design - Zhou, Yong Zhi; Alany, Raid; Chuang, Victor; Wen, Jingyuan (Informa Healthcare, 2013)
The aim of this work was to prepare L-DOPA loaded poly(d,l-lactide-co-glycolide) (PLGA) nanoparticles by a modified water-in-oil-in-water (W1/O/W2) emulsification solvent evaporation method. A central composite design was applied for optimization of the formulation parameters and for studying the effects of three independent variables: PLGA concentration, polyvinyl alcohol (PVA) concentration and organic solvent removal rate on the particle size and the entrapment efficiency (response variables). Second-order models were obtained to adequately describe the influence of the independent variables on the selected responses. The analysis of variance showed that the three independent variables had significant effects (p < 0.05) on the responses. The experimental results were in perfect accordance with the predictions estimated by the models. Using the desirability approach and overlay contour plots, the optimal preparation area can be highlighted. It was found that the optimum values of the responses could be obtained at higher concentration of PLGA (5%, w/v) and PVA (6%, w/v); and faster organic solvent removal rate (700 rpm). The corresponding particle size was 256.2 nm and the entrapment efficiency was 62.19%. FTIR investigation confirmed that the L-DOPA and PLGA polymer maintained its backbone structure in the fabrication of nanoparticles. The scanning electron microscopic images of nanoparticles showed that all particles had spherical shape with porous outer skin. The results suggested that PLGA nanoparticles might represent a promising formulation for brain delivery of L-DOPA. The preparation of L-DOPA loaded PLGA nanoparticles can be optimized by the central composite design.